2014
DOI: 10.3748/wjg.v20.i25.8320
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal lymphangiomatosis in a 38-year-old female: Case report and literature review

Abstract: Lymphangioma is an uncommon benign tumor that develops in the lymphatic system. Abdominal lymphangiomatosis is extremely rare in adult patients, and the clinical symptoms of this condition are complicated and atypical. We report a case of abdominal lymphangiomatosis in a 38-year-old female who presented with intestinal bleeding and protein-losing enteropathy, as well as lesions in the lung and bones. A computed tomography scan revealed multiple small cystic lesions without enhancement. Histological examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…GLA can manifest from a localized disease consisting of endothelium‐lined spaces to a more extensive lesion involving different organs . A rare and interesting finding in our case was chylous rhinorrhea.…”
mentioning
confidence: 61%
“…GLA can manifest from a localized disease consisting of endothelium‐lined spaces to a more extensive lesion involving different organs . A rare and interesting finding in our case was chylous rhinorrhea.…”
mentioning
confidence: 61%
“…The brain is the one exception, as it lacks lymphatic channels (9)(10)(11). Lymphangioma classification is divided into four categories: capillary lymphangioma, cavernous lymphangioma, cystic lymphangioma, and hemolymphangioma (12). Diffuse lymphangiomas involving the skin occasionally occur in children, and this condition is called generalized lymphangiomatosis (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…Jain et al reported a 15-year-old female patient with small-bowel lymphangioma. Lin et al reported a 38-year-old female patient with duodenal lesions (12,19). Our patient was a 44-year-old female with lymphangiomas of the ileum and jejunum.…”
Section: Discussionmentioning
confidence: 99%
“…Any part of the mediastinum can be affectedanterior, middle, posterior, and superior, perhaps with slight prevalence in the anterior part and there is well defined multilocular water density mass with or without compression or displacement of nearby structures. [9][10][11] Pulmonary function tests may be used to help diagnose diffuse pulmonary lymphangiomatosis. Affected individuals often have a restrictive pattern or a mixed restrictive and obstructive pattern.…”
Section: Workupmentioning
confidence: 99%